INTEGRATING AL-QUR’AN TEXTS IN ISLAMIC RELIGIOUS EDUCATION (IRE) LEARNING IN PRIMARY SCHOOLS: A MULTI-SITE STUDY IN FIVE PUBLIC PRIMARY SCHOOLS IN SOUTH BUTON REGENCY - La Jusu; La Sugi; Sulasri Sulasri; Ayu Wulandari; Salmawati Salmawati (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study examines the patterns of Al-Qur’an text use in Islamic Religious Education (IRE) learning in five public primary schools in South Buton Regency, the obstacles to its implementation; and its contribution to students' understanding of Islamic teachings, the formation of religious character, and religious literacy. The study employs a qualitative approach with a collective multi-site case study design in Grade V classes. Data were collected through non-participant classroom observations, semi-structured interviews with IRE teachers and students in each school, and a review of learning documents. Data were analyses thematically through data condensation, data display, and conclusion drawing–verification (with explicit comparisons of patterns across sites. The findings reveal three main themes: (1) relatively consistent patterns of Al-Qur’an text use across the five schools—including devotional opening routines, selection of verses aligned with the lesson topic, and guided reading/tajwid practice—with variations in intensity and in the schools' religious programmes; (2) similar pedagogical and structural constraints, such as limited time allocation, diverse levels of Al-Qur’an reading ability, limited media and contextual resources, and difficulties in facilitating the applied understanding of verses, which are further shaped by differences in facilities and local religious ecosystems; and (3) contributions to the strengthening of conceptual understanding of IRE, the internalisation of values and religious habits, and the development of students' religious literacy, with comparatively more substantial outcomes in schools that have additional religious programmes and strong parental support. These findings underscore the importance of differentiated instruction in Al-Qur’an reading ability, the strengthening of learning media, and school–parent collaboration tailored to each school's context so that Al-Qur’an text use does not stop at recitation but leads to meaningful understanding and more measurable behavioural change.